2022
DOI: 10.3390/v14081659
|View full text |Cite
|
Sign up to set email alerts
|

Finding Asymptomatic Spreaders in a COVID-19 Transmission Network by Graph Attention Networks

Abstract: In the COVID-19 epidemic the mildly symptomatic and asymptomatic infections generate a substantial portion of virus spread; these undetected individuals make it difficult to assess the effectiveness of preventive measures as most epidemic prevention strategies are based on the detected data. Effectively identifying the undetected infections in local transmission will be of great help in COVID-19 control. In this work, we propose an RNA virus transmission network representation model based on graph attention ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Our research mainly focuses on COVID-19, an urgent problem to solve in 2022 with the emergence of multiple SARS-CoV-2 variants that can escape human immunity elicited by previous infection or vaccination [ 16 , 17 ]. Du et al and Jin et al reviewed and estimated the reproduction number of SARS-CoV-2 variants (e.g., Omicron, Delta) to evaluate their transmission advantages [ 16 , 18 ] and found that asymptomatic spreaders could be identified from the transmission network [ 19 ]. Mass vaccination, treatment, and mass testing can help reduce the overall population-level attack rate and prove critical to early pandemic mitigation.…”
mentioning
confidence: 99%
“…Our research mainly focuses on COVID-19, an urgent problem to solve in 2022 with the emergence of multiple SARS-CoV-2 variants that can escape human immunity elicited by previous infection or vaccination [ 16 , 17 ]. Du et al and Jin et al reviewed and estimated the reproduction number of SARS-CoV-2 variants (e.g., Omicron, Delta) to evaluate their transmission advantages [ 16 , 18 ] and found that asymptomatic spreaders could be identified from the transmission network [ 19 ]. Mass vaccination, treatment, and mass testing can help reduce the overall population-level attack rate and prove critical to early pandemic mitigation.…”
mentioning
confidence: 99%